TEACHING STRATEGIES OF CIVICS TEACHERS IN INSTILING DISCIPLINE IN THE LEARNING PROCESS AT MAN 1 SAMARINDA - Ana Rahayu; Aloysius Hardoko; Alim Salamah; Jamil (SOSIOEDUKASI, 2025)
This study aims to describe the learning strategies used by Civic Education teachersin instilling discipline in students at MAN 1 Samarinda. This study uses a descriptivequalitative approach with data collection techniques through interviews, observation,and documentation. The results show that Civic Education teachers apply disciplineinstilling strategies through exemplary behavior, habit formation, rewards, andeffective communication. Teachers consistently demonstrate discipline inattendance, time management, and task implementation, thereby setting a positiveexample for students. Through the application of these strategies, students showedan increase in discipline in attending classes, collecting assignments on time, andobeying class rules. This proves that the strategies used by Civic Education teachersare effective in instilling discipline in the learning process and have a real impact oncreating an orderly, active, and responsible learning atmosphere in the classroom.